Automated Inventory Tracking and Alert System - R., Parthiban; S., Bincy; D., Ilamathi; T., Deva Priya (Journal of Electrical Engineering and Automation, 2025)
The research is on inventory management systems, focusing on IoT-based solutions, RFID technology, and machine learning applications. The study examines various systems, including automated inventory tracking, real-time monitoring, and predictive analytics for demand forecasting. The survey highlights the benefits of these systems, such as improved inventory accuracy, reduced stockouts, and enhanced customer satisfaction. However, it also discusses challenges and limitations, including dependency on network connectivity, initial setup costs, and data accuracy concerns. This survey provides a comprehensive overview of the current state of inventory management systems, identifying opportunities for future research and development.